CROSS CULTURAL COMMUNICATION TO ACCOMODATE GENERATION GAP IN DISRUPTIVE ERA - Bhernadetta Pravita Wahyuningtyas; Ulani Yunus; Mario Nugroho Willyarto (Master of Communication Science Program, Universitas Diponegoro, 2021)
This research described about how Cross-Cultural Communication contributes its influence on accommodating the generation gap to improve a social structure in Indonesia, especially on Disruptive Era. In accommodating the generation gap, the cross-cultural communication focus on the patterns of convergence and divergence of communication behaviors, particularly as they relate to the goals of the people for social approval, communication efficiency, and identity. This research was done in Bina Nusantara (BINUS) University, and used a descriptive qualitative method with constructivism paradigm, and coding to analyze the data. The results showed that accommodation in cross-cultural communication can improved the ability on problem-solving skills, collective decisions and can resolved the problem that arise from generation gap to make it become harmonious interactions. The lack of the role in providing information from generation to another generation usually based on the assumption that the other generation already knew the condition, situation and also the meaning behind it as well without any discussion and deeper communication further. Due to the changes in social structure, BINUS creating a cross cultural communication model to accommodate the generation gap in social structure: openness, and engagement, through (for example) creative furniture arrangemement in some classes. The result also shown that engagement between the students and the lecturer will be more powerful in creating values to have a better social condition. The people who willing to build the communication instead of assumed will be more successful in all aspects of cross-cultural communication.